The productive and receptive knowledge of collocations by advanced Arabic-speaking ESL/EFL learners - Alsakran, Rayed A., author; Flahive, Douglas, advisor; Ehlers-Zavala, Fabiola, committee member; Grim, Frederique, committee member (Colorado State University. Libraries, 2011)
Although it is widely acknowledged that collocations play an important role in the field of second language acquisition, a number of previous studies have reported students' lack of collocational competence and the difficulties they encounter in learning and using collocations. The present study examines the productive and receptive knowledge of lexical and grammatical collocations among advanced Arabic-speaking learners of English. Furthermore, it investigates whether the language environment (ESL or EFL) has an influence on the acquisition of collocations. It also explores whether there is a significant difference between participants' performance on three types of collocations: verb-noun, adjective-noun, and verb-preposition. Data for this study were collected from 68 participants: 38 Saudi students at the Institute of Public Administration in Riyadh, Saudi Arabia, and 30 Arab students in the Intensive English program at Colorado State University. The participants' productive collocational knowledge was measured by three gap-filling tests: verb-noun and adjective-noun collocation tests where the initial letter of the collocant was provided and a verb-preposition collocation test where the meaning of the phrasal verb was supplied. Their receptive collocational knowledge was measured by an appropriateness judgment test in which participants have to circle the number corresponding to the underlined part of a sentence that is judged unacceptable. The results of the statistical analysis revealed that participants' learning environment has a strong effect on the acquisition of L2 collocations. The ESL learners had significantly higher scores than the EFL learners. Moreover, there was a significant difference between the participants' productive and receptive knowledge of collocations. The participants' productive knowledge of collocations lagged far behind their receptive collocational knowledge. The findings also revealed a statistically significant difference between the three types of collocation. The participants performed far better on the verb-noun collocations test than on the adjective-noun and verb-preposition collocations tests. Overall, the results showed that Arabic-speaking learners of English demonstrated poor knowledge of collocations on the four tests. The study concludes with pedagogical implications, limitations, and suggestions and recommendations for future research.